Pathological and molecular study of mycotic abortion in ewes - Bushra Hamza Faris; Mohammed J. Alwan; Ban Abbass Abdulmajeed (Kufa Journal for Veterinary Medical Sciences, 2013)
The aims of the present study is  to isolate the fungal species associated with ewe abortion and to examine the histopathological  changes in the placenta associated with fungal isolates .In addition to study the genetic information  of TNF alpha gene, intensity and score of TNF-alpha  protein in  aborted and normal placenta by PCR and IHC respectivly.